(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present work was carried out to explore the qualitative analysis of bioactive phyto-constituents present in methanolic extracts of five toxic plant seeds by using gas chromatography-mass spectrometry. The analysis of extracts revealed the presence of the different biologically active compounds including alkaloids, glycosides, flflavonoids, phenols, fatty acid, ester, epoxide, steroids, and protein etc. Forensic toxicological chemistry deals with the chemistry and analysis of various types of poisons including plants. Diagnosing plant poisoning especially their seeds can be difficult and must be quickly done. In conclusion, the recovery of various toxic and therapeutically constituents could be helpful for forensic toxicologist.